Effectiveness of Flip Chart Media in Increasing Abilities of Wudhu for Mild Mental Retardation Children - Suci Wulan Dari; Megaiswari Megaiswari (EDUCATIO : Journal of Education, 2019)
This research reveals that a mild mental retardation child does not yet know the proper ablution procedures, this is seen when the researcher observes when the child takes ablution 'before performing midday prayer in congregation, when taking ablution' the child only performs carelessly not according to correct ablution 'procedure. This study aims to prove whether the flip chart media is effective in enhancing the ability to perform ablutions' mild retarded children. The research method in this research is a Single Subject Research (SSR), with the designation A-B-A. Measure and collect data at baseline conditions (A1), provide intervention (B) using flip chart media and provide baseline conditions (A2). The data analysis technique uses a visual graph analysis. Measurement of variables using a percentage of the number of instruments. The results showed that there was an increase in the ability to perform ablution in a positive manner, where the baseline conditions (A1) and intervention (B) Overlap was 0%, and the baseline conditions (A2) and intervention (B) Overlap was 57.14%. The smaller the percentage of Overlape, the better the effect of intervention /treatment on behavior change. Based on these results it shows that the flip chart media is effective in enhancing the ability to perform ablutions' mild retarded children.